Analisis Manajemen Pelatihan Kader Malaria Pada Populasi Suku Anak Dalam Di Kabupaten Musi Rawas Utara - Elita Sari; Rizma Adlia Syakurah (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Malaria remains a public health issue in Indonesia due to the favorable climate for mosquito breeding. Various policies have been implemented to combat the spread of malaria, including training malaria cadres. The Anak Dalam tribe is one of the tribes that has received malaria awareness training. This training, conducted through local malaria cadres, aims to enhance the tribe's knowledge about malaria. The project management approach method is employed for this activity, which took place on June 20, 2022, at the Muara Rupit Health Center from 08.00-12.30 am and was attended by health cadres. Given the nomadic nature of the Anak Dalam Tribe and the vulnerability of their home environment to malaria transmission, cadre training becomes crucial. The activity is carried out in five stages: initiation, planning, implementation, monitoring and supervision, and evaluation and reporting. The initiation process involves identifying and examining the problems at hand. Planning is conducted by forming work teams and coordinating implementation-related activities. The training sessions were delivered by several speakers from the South Sumatra Provincial Health Office. The activities are carefully monitored and evaluated to ensure smooth progress. Once all activities are completed, a comprehensive report is prepared. Despite encountering challenges during the activity, the health cadres actively participated in the training.